Performance in a Science test of lecture taught and flipped class - taught students: towards improved instructions - Leyco, Laureen F.; Orcacion, Aeron B. and Sibonga, Lester P. 4 0 16; 5 (2018)
ABSTRACT: This research study aimed to know the performance of the students in a Science Test after using Lecture method and Flipped Classroom Method in two homogenous classes in teaching Science in a public high school. The raw scores resulted from the pre test and the post-test examinations were gathered as a support to this study. The research design employed in the study is quasi-experimental, where the research participants were selected randomly comprising the control group and the experimental group. The research instruments implemented in the study were the lesson plans and visual aids for both groups and the video resources for the experimental group. Uniform pre-test and post-test examinations were also utilized establishing the reliability of the data collected. The researchers used a variety of statistical tools such as mean, standard deviation, T-test for equal and unequal variances. It took a week for the researchers to conduct the study. After the implementation of the research study, they found out through the pre-test that the students from the both groups have no prior knowledge regarding the topic discussed and the experimental group performed better in terms of the result of their posttest examinations.
Thesis: (Bachelor of Secondary Education with Specialization in Biological Sciences)- Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2